(untitled) (Research, Society and Development, 2020)
This work aimed to study beverages’ storage stability based on cashew apple pulp and honey during 120 days. Three formulations were prepared: F1 (75% of cashew apple pulp and 25% of honey; F2 (60% of cashew apple pulp and 40% of honey) and F3 (50% of cashew apple pulp and 50% of honey). The formulation F1 showed the highest content of ascorbic acid after storage (95.74 mg.100mL). The pH did not show variation between the formulations studied. Soluble solids showed significant differences during storage and were consistent with the drink’s honey content, ranging from 28.8 to 30.0 for F1, from 36.5 to 40.1 for F2, and 44.3 to 47.7 for F3. The content of carotenoids and phenolic compounds decreased during storage time. The preparation of beverages based on cashew apple and honey presented an alternative to adding value to the cashew apple pulp.